1996
DOI: 10.1073/pnas.93.12.5720
|View full text |Cite
|
Sign up to set email alerts
|

Adenylate kinase complements nucleoside diphosphate kinase deficiency in nucleotide metabolism.

Abstract: Nucleoside diphosphate (NDP) kinase is a ubiquitous nonspecific enzyme that evidently is designed to catalyze in vivo ATP-dependent synthesis of ribo-and deoxyribonucleoside triphosphates from the corresponding diphosphates. Because Escherichia coli contains only one copy of ndk, the structural gene for this enzyme, we were surprised to find that ndk disruption yields bacteria that are still viable. These mutant cells contain a protein with a small amount NDP kinase activity. The Cells. Cell extracts obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 38 publications
(30 reference statements)
3
80
0
Order By: Relevance
“…It is possible that, in the absence of a genuine NDP kinase activity, low substrate-specificity kinases could provide the necessary (d)NTPs required for normal growth and reproduction . Interestingly, adenylate kinase was identified as the enzyme responsible for the NDP kinase activity detected in Escherichia coli ndk mutants (Lu and Inouye, 1996). Later, it was found that adenylate kinase from Mycobacterium tuberculosis also has NDP kinase activity (Meena et al, 2003).…”
Section: Purine and Pyrimidine Nucleotide Pathways In Mollicutesmentioning
confidence: 99%
“…It is possible that, in the absence of a genuine NDP kinase activity, low substrate-specificity kinases could provide the necessary (d)NTPs required for normal growth and reproduction . Interestingly, adenylate kinase was identified as the enzyme responsible for the NDP kinase activity detected in Escherichia coli ndk mutants (Lu and Inouye, 1996). Later, it was found that adenylate kinase from Mycobacterium tuberculosis also has NDP kinase activity (Meena et al, 2003).…”
Section: Purine and Pyrimidine Nucleotide Pathways In Mollicutesmentioning
confidence: 99%
“…The nucleotide specificity of 14-3-3 proteins was examined by incubation at 37°C for 6 h in Buffer B (100 mM HEPES-KOH, pH 8, 1 uCi of [y- 32 P]ATP, 6 mM MgCl 2 ) with 33 pmol (calculated as a monomer with a mean molecular mass of 30 kDa) of 14-3-3 and 0.5 mM concentrations of various ribo-or deoxyribo-nucleoside diphosphates as phosphate acceptors in 20 ul of reaction mixture [24]. After incubation, the nucleotides were resolved by polyethylene-imi-no-cellulose TLC in 0.75 M KH2PO4, pH 3.5, and quantified with an imaging analyzer.…”
Section: Nucleotide Specificity Of 14-3-3 As Phosphate Acceptormentioning
confidence: 99%
“…The requirement for NTPs and dNTPs, during stress conditions, might be getting mediated through the marginal modulation of the levels of T2. Nevertheless, NDK is nonessential for most bacterial systems, including M. tuberculosis [20], as other enzymes such as adenylate kinase [52] and polyphosphate kinase [53,54], which are present in M. smegmatis also (TIGR Database), might be able to synthesise NTPs and dNTPs, as in E. coli [52,53]. Therefore, M. smegmatis may not be entirely dependent on NDK modulation for NTPs and dNTPs and this may probably be the reason for the lack of significant modulation of NDK.…”
Section: Discussionmentioning
confidence: 99%